Fatigue life improvement in fatigue-aged fastener holes using the cold expansion technique - Zhang, Xiang; Wang, Z. (Elsevier Science B.V., Amsterdam., 2003)
The use of cold expansion process as a life extension technique on aircraft structural joints was investigated. The primary focus was an experimental test programme consisting of open-hole and low-load transfer joint specimens made of 2024-T351 aluminium alloy and pre-fatigued to 25, 50 and 75% of the baseline fatigue life for plain holes. The FALSTAFF loading spectrum was applied. The results indicate that significant life improvements can be obtained through cold expansion applied at all percentages of fatigue life tested in this work with the optimum stage being around 25% of the baseline life. The major life extension was obtained through slower crack growth in the short crack stage. The life improvement factors for the open-hole and joint specimens were comparable provided that the degree of cold expansion is the same. Crack growth life of the open-hole specimen was predicted by employing an analytical residual stress model and the AFGROW computer code. The prediction results showed good agreement with the experimental results for cold expansion at build cases.
Keywords: Fastener holes; Cold expansion; Residual stress